Banks, stock market and economic growth in developing countries: a re-assessment using panel cointegration approach - Abubakar , Abdulsalam; Kassim, Salina (2014)
This study employs the panel co-integration and Fully Modified Ordinary Least Squares (FMOLS) techniques to empirically investigate the impact of financial development on economic growth in 20 developing countries. Based on data covering the period from 1989 to 2010, the results show that the contribution of intermediated funds to the growth process is relatively more significant than that of the stock market. Banks and stock markets are found to be substitute rather than compliment in financing economic activities in these countries, suggesting the availability of alternative financing for the economy. Generally, financial development is found to be important contributors to the growth process. However, overall financial depth represented by the ratio of broad money to GDP is found to be more significant than both banks and stock market in financing real GDP, suggesting that self-finance still dominates as mode of financing in developing countries